Where neoliberalism shapes Confucian notions of child rearing: Influencers, experts and discourses of intensive parenting on Chinese Weibo. (March 2022) - Zhao, Wenting; Bouvier, Gwen
Abstract: In this paper, we use Multimodal Critical Discourse Analysis to look at the posts of influencers using parenting hashtags on Chinese Weibo. It has been observed that motherhood more widely has become a site of discursive tension, often played out online. In this case, we find such tension between former, more Confucian roles of motherhood, related to duty and knowing one's place, and a more recently arrived influence of neoliberalism. On the one hand, the hashtags provide a sense of community for stay-at-home mothers who have given up their careers, but on the other, the influencers configure this duty and obligation into something based on striving, individual success and self-management. They appear to play a role in helping this ideology enter into the family.